Jenis-Jenis Kumbang Tinja (Coleoptera: Scarabaeidae) di Kawasan Cagar Alam Lembah Harau, Sumatera Barat - Rahmatika Putri; - Dahelmi; Henny Herwina (Universitas Andalas, 2014)
A study on dung beetle (Coleoptera: Scarabaeidae) at Lembah Harau Nature Reserve was conducted from July to September 2013. The aim of this study was to identify dung beetles species at the Nature Reserve. We used pitfall trap to collect the beetle along three tracking paths from 500 to 800 asl. We successfully collected 539 individual dung beetles those belong to 18 species, eight genera, six tribes and two subfamilies. Eleven species (61,1 %) of the beetles was not reported in previous study in Indonesia. This suggest to further exploration using various method in various habitat types are necessary.Keyword : dung beetle, Scarabaeidae, Lembah Harau, West Sumatra